EFFECT OF DUST DEPOSITION ON THE PERFORMANCE OF PHOTOVOLTAIC PANELS - Mamarasulova, Hanifa (Физико-технологического образование, 2024)
It is well known that the solar energy is converted into electrical energy directly using semiconductor materials used in photovoltaic (PV) panels. Despite great advances in semiconductor materials technology, panel efficiency has remained quite low in recent years. Panel performance is affected by many factors such as tilt angle, shading, dust, solar radiation, temperature and conductor losses. In this work, a preliminary study was conducted on the effect of dust deposition on the performance of a PV system. The research included indoor simulations of the panels as well as experiments with the panels in an outdoor test bed. The effect of dust on the performance characteristics of the panels was studied by obtaining the current-voltage characteristics of identical panels that were under the same conditions of insolation and ambient temperature, while one of the panels retained dust on its surface, and the other was cleaned of dust